Knowledge, Attitude, and Practice towards Hepatitis B Virus among Pregnant Women Attending Antenatal Care at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. (16th January 2020) - Gebrecherkos, Teklay; Girmay, Getu; Lemma, Mulualem; Negash, Markos
Abstract : Background . Hepatitis B virus (HBV) infection remains a serious public health concern worldwide. Mother-to-child transmission (MTCT) is the major mode in endemic areas, including Ethiopia, where little is known about pregnant women's knowledge, attitudes, and practice towards HBV infection and MTCT. Therefore, the study is aimed at determining the knowledge, attitude, and practice towards HBV among pregnant women attending antenatal care. Method . A cross-sectional study was conducted from February to April 2018, at the University of Gondar Comprehensive Specialized Hospital. A total of 354 pregnant women were selected by systematic random sampling and included in this study. KAP of participants on HBV MTCT was assessed using a structured questionnaire. Data was analyzed using SPSS version 22 software. Result . The total response rate was 100% (354/354). Out of the 354 participants, 73.4% were within the poor knowledge. Only 18.9% of the respondents know HBV can be transmitted from mother to child during pregnancy. Less than half (43.8) of the participants think that they will never be infected with HBV, and 47.7% of them go to traditional healers when they have symptoms of HBV. Majority of the respondents (85.87%) had never screened for HBV, and only 28.5% of the participants believed that hepatitis B can cause liver cancer. In multivariable analysis, residence, income, and educational level were associated with mean score knowledge and attitude. Conclusions . Knowledge about HBV among pregnant women was found to be poor, and their attitude and practice were also limited. Therefore, extensive health education program should be given to the pregnant women to increase their awareness towards HBV infection. All pregnant women should be screened for HBV as part of ANC follow-up.